Development and use of Сherenkov-type detectors for measurements of fast electrons in tokamaks - Rabiński, M.; Jakubowski, L.; Żebrowski, J.; Sadowski, M.J.; Malinowski, K.; Mirowski, R.; Jakubowski, M.; Plyusnin, V.V.; Lotte, Ph.; Pascal, J-Y. (Вопросы атомной науки и техники, 2012)
The paper reports on progress in design and use of novel detectors for experimental studies of fast (run-away and ripple-born) electrons in various experiments of the tokamak type. The idea of the use of a Cherenkov effect for direct on-line measurements of the fast electrons within tokamaks was presented by scientists from the NCBJ (former IPJ) several years ago. Successive efforts led to the development of prototype detector heads equipped with diamond or aluminium nitrate (AlN) crystals, which were shielded with very thin metal filters in order to eliminate the visible light from plasma and to enable a rough energy analysis of electrons. Those Cherenkov radiators were coupled through optical-fibre cables with fast photomultipliers. Those prototypes were applied for test measurements within the CASTOR experiment in Prague, and later in the ISSTOK device in Lisbon, but the main aim remained to develop the Cherenkov detectors for the TORE-SUPRA experiment in Cadarache.